2022
DOI: 10.3390/ijms232112734
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Action of Coumarin Derivatives through Activation of TRKB-CREB-BDNF Pathway and Reduction of Caspase Activity in Neuronal Cells Expressing Pro-Aggregated Tau Protein

Abstract: Hyperphosphorylation and aggregation of the microtubule binding protein tau is a neuropathological hallmark of Alzheimer’s disease/tauopathies. Tau neurotoxicity provokes alterations in brain-derived neurotrophic factor (BDNF)/tropomycin receptor kinase B (TRKB)/cAMP-response-element binding protein (CREB) signaling to contribute to neurodegeneration. Compounds activating TRKB may therefore provide beneficial effects in tauopathies. LM-031, a coumarin derivative, has demonstrated the potential to improve BDNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…As mentioned above, the hyperphosphorylation of Tau and its aggregation are typical neuropathological hallmarks of AD. Lin et al (2022) examined the protective effects of analogous compounds of LM-031 (a coumarin derivative) on SH-SY5Y cells expressing ΔK280 tauRD-DsRed folding reporter [ 62 ]. ΔK280 tauRD is a deletion mutation of Tau found in patients with tauopathies [ 63 , 64 ].…”
Section: Bdnf/trkb System and Neuroprotection Drug Candidates For Admentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the hyperphosphorylation of Tau and its aggregation are typical neuropathological hallmarks of AD. Lin et al (2022) examined the protective effects of analogous compounds of LM-031 (a coumarin derivative) on SH-SY5Y cells expressing ΔK280 tauRD-DsRed folding reporter [ 62 ]. ΔK280 tauRD is a deletion mutation of Tau found in patients with tauopathies [ 63 , 64 ].…”
Section: Bdnf/trkb System and Neuroprotection Drug Candidates For Admentioning
confidence: 99%
“…Using theΔK280 tauRD-DsRed SH-SY5Y, the authors found that the LM-031 analogs LMDS-1 to -4 reduced Tau aggregation. They also found that LMDS-1 and LMDS-2 decreased the activity of caspase-1, caspase-6, and caspase-3, and the effect was reversed after the knockdown of TrkB, suggesting involvement of the BDNF/TrkB system in neuroprotection by LM-031 analogs [ 62 ]. Using SH-SY5Y cells expressing Aβ-GFP, the protective effects of the LM-031 analogs LMDS-1 to -4 have also been demonstrated.…”
Section: Bdnf/trkb System and Neuroprotection Drug Candidates For Admentioning
confidence: 99%
“…Coumarin compound LM-021 [15] was synthesized and analyzed as described [19]. LMDS-1 and LMDS-2 [17] were obtained from Enamine (Kyiv, Ukraine). Tafamidis was supplied by Cayman Chemical (Ann Arbor, MI, USA).…”
Section: Compoundsmentioning
confidence: 99%
“…LM-021 is a synthetic coumarin-chalcone derivative with anti-aggregatory, antioxidant, and neuroprotective effects in Alzheimer's Disease (AD) cell models [15]. LMDS-1 and LMDS-2, analogs of LM-031 (a synthetic coumarin-chalcone derivative), were likely to work as tropomyosin receptor kinase B (TRKB) agonists to exert neuroprotection in AD disease cell models [16,17]. Tafamidis is a compound that is commonly used to treat transthyretin amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylated CREB has been shown to induce the transcription of the anti-apoptotic regulator, B-cell lymphoma 2 (Bcl-2) [ 17 ] and decrease the expression of the pro-apoptotic mediators, Bcl-2-associated X protein (BAX) and Caspase-3 [ 18 , 19 ]. Moreover, BDNF reduces the levels of the hyperphosphorylated tau protein [ 20 ] which may represent a key player in the cognitive dysfunction in autistic subjects [ 21 ].…”
Section: Introductionmentioning
confidence: 99%